Fiqih Learning Implementation Through Google Classroom During The Pandemic Covid-19 Class X IPA In MA Al-Muhajirin - Sumeilina, Sumeilina; Fitriyani, Fitriyani; Arikarani, Yesi; Amirudin, Muhamad Faizul; Mukmin, Taufik (Edification Journal : Pendidikan Agama Islam, 2022)
Covid-19 is one of the problems affected by all sectors, especially the education sector. During the pandemic, all teaching and learning activities that started face-to-face must now be transferred to online learning. Technology is one of the most important things in the education sector, especially during the online learning period. So that initially technology was only used by some people, now almost all education actors use both teachers and students, the problem is that many students and teachers do not have the same facilities. From this, the authors are interested in researching a study entitled, Implementation of Fiqh Learning Using Google Classroom during the Covid-19 Pandemic Period in Class X IPA at Madrasah Aliyah Al-Muhajirin, Musi Rawas Regency. The data from this study were obtained by the author using the interview method conducted to class X fiqh teachers and class XI and XII fiqh teachers. The conclusion of this study shows that online learning in fiqh learning is carried out briefly, and simply begins with an opening greeting. The material presented is only in the form of videos and students are instructed to understand independently. The evaluation process is also fairly simple, which is done through the Google Classroom application, whose grades can be seen at any time, both by teachers and students.